Learning Motivation and Parenting Styles of Parents and Their Relationship to Social Studies Learning Outcomes for Elementary School Students - N. K. Sri Anggreni; I K. Dibia (Universitas Pendidikan Ganesha, 2021)
The problem of this research is the variation in student social studies learning outcomes. There is a tendency caused by two factors: learning motivation as an internal factor and parenting as an external factor. This study analyzes parents' learning motivation and parenting styles on students' social studies learning outcomes. This type of research is Expo facto research. The population is 49 students. The population was taken using a saturated sample (study population). Data were collected using questionnaires and document recording. Data were analyzed by regression analysis technique. The prerequisite test for regression analysis and hypothesis testing uses simple regression, product-moment correlation, and multiple regression. The results showed a real and positive relationship between parenting styles and social studies learning outcomes. This was indicated because the R-count (0.449) > from r-table 5% = (0.233) was significant. Simultaneously, it was found that there was a relationship between learning motivation and parenting styles on social studies learning outcomes. It can be seen that r count 0.740 > r table 0.233 as well as based on the results of testing with the F test (simultaneously) with = 5% then it can be seen that the learning motivation and parenting styles of parents are simultaneously significantly related to social studies learning outcomes. The research implications are related to the second problem, namely the relationship between parenting styles and students' social studies learning outcomes.